Optimum light conditions for larval rearing of tiger grouper Epinephelus Fuscoguttatus - Mukai, Yukinori; Mohammad Seth, Siti Nasihin (Universiti Malaysia Sabah, 2013)
Optimum light conditions are essential to reduce fish stress and obtain high growth rate under cultivating conditions. There are many studies about light intensities for larval rearing. However, there are only few studies about light wavelength and light intensities of each wavelength for larval rearing. Tiger grouper, Epinephelus fuscoguttatus is an important fish species for aquaculture in Southeast Asia. This study was conducted to examine the optimum light wavelength and intensity for tiger grouper larvae using LED lamps. Tiger grouper larvae were obtained from the IIUM hatchery. The larvae were reared in 40L aquarium in dark rooms, using white (control), blue, green, yellow, and red light emitting diodes (LED). The larvae were reared under 0.38, 1.7 and 8.7 µmoles/m²/s for each wavelength. Each condition had triplicate. The temperature was maintained at 27.5-28.5oC. Larvae were sampled to examine the survival rate and growth rate. Nannochlropsis sp.were added starting 0 days post hatching (DPH) onwards at the density of 1million cells/ml. Feeding started at one day old. Results showed that short wavelength lights (blue and green) had tendency of higher survival rate compared to longer wavelength lights (yellow and red) for tiger grouper larvae.